2014
DOI: 10.2298/zmspn1426025j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and time on deoxynivalenol (DON) and zearalenone (ZON) content in corn

Abstract: Fumonisins are Fusarium mycotoxins that occur in corn and corn-based foods and they have been implicated in several animal and human diseases. Their effect on human health is unclear, however, fumonisins are considered to be risk factors for cancer. Baking, frying, and extrusion cooking of corn at high temperatures (190?C) reduce fumonisin concentrations in foods, with the amount of reduction achieved depending on cooking time, temperature, recipe, and other factors. The aim of this work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A 30‐min roasting of whole (naturally contaminated) kernels at 180 to 220 °C lowered ZEN levels by 14 to 33% and DON by 7 to 36%, with higher reductions at higher temperature (Pleadin et al., 2019). During heating of ground maize at 200 or 220 °C for 15 to 20 min, ZEN was lowered by approximately 22 to 27% and DON by approximately 12 to 15% (Jauković, Stanišić, Nikodijević, & Krnjaja, 2014). Here, reduction was higher at longer heat treatment, whereas no significant difference was found between 200 and 220 °C.…”
Section: Effects Of Secondary Food Processing On Mycotoxin Levels In mentioning
confidence: 99%
“…A 30‐min roasting of whole (naturally contaminated) kernels at 180 to 220 °C lowered ZEN levels by 14 to 33% and DON by 7 to 36%, with higher reductions at higher temperature (Pleadin et al., 2019). During heating of ground maize at 200 or 220 °C for 15 to 20 min, ZEN was lowered by approximately 22 to 27% and DON by approximately 12 to 15% (Jauković, Stanišić, Nikodijević, & Krnjaja, 2014). Here, reduction was higher at longer heat treatment, whereas no significant difference was found between 200 and 220 °C.…”
Section: Effects Of Secondary Food Processing On Mycotoxin Levels In mentioning
confidence: 99%
“…In the same way, it was reported that oil popping (frying of the grains in oil) does not affect DON levels [ 11 ]. Jaukovic et al have shown that, at 200 °C, DON contents are reduced by 12% after 15 min and by 15% after 20 min of heating [ 16 ]. By contrast, another study reported more important reductions after frying flour artificially contaminated with DON.…”
Section: Introductionmentioning
confidence: 99%
“…DON exerts its toxic effects through inhibition of eukaryotic protein synthesis by binding to the 60S subunit of the ribosome (Hassan et al, 2015). Owing to its remarkable chemical stability and high thermostability (170–350°C), conventional chemical/physical methods do not achieve effective DON decontamination (Jaukovic et al, 2014). Thus, a feasible and sustainable approach to address accidental DON contamination of food and feed commodities is urgently needed.…”
Section: Introductionmentioning
confidence: 99%